Catherine Colomb's VISION OF TIME: in Dialogue with Marcel Proust and Virginia Woolf - Barbakadze, Tamar (Peter Lang International Academic Publishers, 2022)
This monograph is the first substantial contribution to the study of the Swiss novelist Catherine Colomb's dialogue with Marcel Proust and Virginia Woolf as well as to time and memory studies. The framework and approach devised to examine Colomb's oeuvre contribute to unravelling some of its complexities, not only in its curving style, ephemeral, and sequence-defying narrative, but also in its literary engagement with the science and philosophy that shaped modernity and proposed new ways of thinking time, knowledge, and the human experience. This thesis ultimately allows us to gain insight into the originality of Colombian time experience, memory, and point-of-view representations, transcending the alleged influence of her iconic predecessors.